Particle Therapy for Non-Small Cell Lung Tumors: Where Do We Stand? A Systematic Review of the Literature - Wink, Krista C. J.; Roelofs, Erik; Solberg, Timothy; Lin, Liyong; Simone, Charles B.; Jakobi, Annika; Richter, Christian; Lambin, Philippe; Troost, Esther G. C. (Frontiers in Oncology, 2014)
This review article provides a systematic overview of the currently available evidence on the clinical effectiveness of particle therapy for the treatment of NSCLC and summarizes findings of in silico comparative planning studies. Furthermore, technical issues and dosimetric uncertainties with respect to thoracic particle therapy are discussed.